2010
DOI: 10.1212/wnl.0b013e3181f39a78
|View full text |Cite
|
Sign up to set email alerts
|

CSF amyloid β 1-42 predicts cognitive decline in Parkinson disease

Abstract: Objective: Cognitive decline associated with Parkinson disease (PD) is common and highly disabling. Biomarkers that help identify patients at risk for cognitive decline would be useful additions to the clinical management of the disease. Methods:A total of 45 patients with PD were enrolled in this prospective cohort study and had at least 1 yearly longitudinal follow-up evaluation. CSF was collected at baseline and cognition was assessed at baseline and follow-up visits using the Mattis Dementia Rating Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
248
7
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(279 citation statements)
references
References 35 publications
(33 reference statements)
21
248
7
3
Order By: Relevance
“…So far, this sort of repeated samples is usually not permitted; however, few recent investigations utilized longitudinal measurements (Siderowf et al, 2010;Hall et al, 2015), obtained at baseline and after 3 years, in order to study if changes of CSF biomarkers correlate with motor progression.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…So far, this sort of repeated samples is usually not permitted; however, few recent investigations utilized longitudinal measurements (Siderowf et al, 2010;Hall et al, 2015), obtained at baseline and after 3 years, in order to study if changes of CSF biomarkers correlate with motor progression.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Authors showed also a significant association between CSF levels of A 1-42 , A 1-40 , A 1-38 and memory impairment. A recent prospective study in a cohort of 45 PD patients with 1-year follow-up showed that lower levels of A 1-42 at baseline were associated with a more rapid cognitive decline (Siderowf et al, 2010). Another recent study reported an association between low levels of A 1-42 levels in 22 non-demented PD patients and worse performance at Digit Symbol test .…”
Section: Classical Csf Biomarkers and Risk Of Cognitive Impairment In Pdmentioning
confidence: 99%
“…The spreading of Lewy body pathology to neocortical regions altogether with AD-type pathology in terms of -amyloid deposits, have been implicated in the pathogenesis of cognitive decline in PD (Braak et al, 2005;Ballard et al, 2006), suggesting an interplay between synucleinopathies and tauopathies. Recently, a growing amount of investigations in PD has focused on CSF biomarkers traditionally used in AD, namely -amyloid 1-42 (A 1-42 ), total tau, hyperphosphorylated tau, in order to improve the ability to detect risk for cognitive impairment and dementia (Sjögren et al, 2002;Mollenhauer et al, 2006;Parnetti et al, 2008;Compta et al, 2009;Alves et al, 2010;Siderowf et al, 2010;Montine et al, 2010;Leverenz et al, 2011) (table 2). Tau protein, a microtubule associated protein, in its phosphorylated form represents the major component of the neurofibrillary tangles (Grundke-Iqbal et al, 1986).…”
Section: Classical Csf Biomarkers and Risk Of Cognitive Impairment In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…In PD, studies have shown normal or decreased levels of CSF Aβ42 in PD [32]. Low levels of Aβ42 in non-demented PD patients have been shown to be associated with future cognitive decline and an increased risk of developing dementia and memory impairment [33].…”
Section: Cerebrospinal Fluid Biomarkersmentioning
confidence: 99%